Weighing Futures Trading Through the Lens of Maqāṣid Al-Syarī'ah: Between Justice, Benefit, and Modern Speculation - Said Agil Al Munawar; Achmad Nursobah; Arifuat Marzuqi (Kartika: Jurnal Studi Keislaman, 2026)
Trading in derivative instruments, particularly futures contracts (futures), is an important part of the modern financial system due to its role in price discovery, risk transfer, and liquidity provision. However, from the perspective of Islamic law, this practice raises serious debates regarding elements of speculation, uncertainty (gharār), and potential injustice that may threaten the objectives of the Sharī‘ah. This article aims to examine futures trading through the maqāṣid al-syarī‘ah approach by emphasizing the principles of justice (al-‘adālah), benefit (maṣlaḥah), and wealth protection (ḥifẓ al-māl). This study employs a qualitative method based on library research with a normative-analytical approach, encompassing classical fiqh literature, contemporary fatwas, standards of international Sharī‘ah institutions, and empirical economic studies. The findings indicate that futures trading cannot be classified as strictly permissible or impermissible, but must be understood contextually and conditionally. Futures may be justified if they function as genuine hedging instruments (hedging), supported by clear underlying assets, information transparency, and limitations on excessive speculation. In contrast, the dominance of high leverage and purely speculative activities tends to contradict the objectives of the Sharī‘ah and may lead to instability and injustice in the economic system